Surprised by Wirecard? Enablers of corporate wrongdoing in Europe - Theo Nyreröd; Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2021)
In the last two decades prolonged instances of corporate wrongdoing in Europe have been un-covered: from Siemens' systemic bribery to HSBC and other major bank's money laundering issues, Dieselgate, LIBOR price-rigging, and the recent Wirecard debacle. What has driven European firms to engage in such systematic wrongdoing? In this article, we first use data on US investigations to identify the European countries hosting most corporate wrongdoers. We then consider these countries' legal, institutional, and political contexts in search for explanations of the main enablers of this behavior, ending with some policy recommendations.
Keywords: K42; K2; 330; corporate wrongdoing; financial fraud; money laundering; corruption; whistleblowers